Burst increases of precipitating electrons recorded by the DEMETER satellite before strong earthquakes - X. Zhang; C. Fidani; J. Huang; X. Shen; Z. Zeren; J. Qian (Natural Hazards and Earth System Sciences, 2013)
This case study developed a method for data processing over six years, from 2004 to 2010, of 70 keV–2.3 MeV electrons recorded by the DEMETER (Detection of Electro-Magnetic Emissions Transmitted from Earthquake Regions) satellite. Short time increases in electron counting rates, having 99% probabilities of not being Poisson fluctuations, were statistically selected using geomagnetic invariant space and called electron bursts. Temporal series were analysed confirming the seasonal variations in low energy bands of 70–450 keV. Differently from previous results, the DEMETER results exhibited two peaks of electron bursts: one in the period June–August and one in the period December–February annually. Specifically, six earthquake cases are presented in detail having increases in electron burst number prior to events. Moreover, electron burst precipitation occurring before each strong earthquake of the entire period over the life of the satellite with M ≥ 7.0 was verified as having a probability greater than 97% of not being of a statistical origin. Low energetic electrons in 70–330 keV resulted occurring more frequently near seismic activity than those observed in 330 keV–2.34 MeV energy bands at the satellite altitude in the ionosphere.